Novel approaches to develop Rift Valley fever vaccines - Indran, Sabarish V.; Ikegami, Tetsuro (Frontiers in Cellular and Infection Microbiology, 2012)
Rift Valley fever (RVF) is endemic to sub-Saharan Africa, and has spread into Madagascar, Egypt, Saudi Arabia, and Yemen. Rift Valley fever virus (RVFV) of the family Bunyaviridae, genus Phlebovirus causes hemorrhagic fever, neurological disorders or blindness in humans, and high rate abortion and fetal malformation in ruminants. RVFV is classified as a Category A Priority pathogen and overlap select agent by CDC/USDA due to its potential impact on public health and agriculture. There is a gap in the safety and immunogenicity in traditional RVF vaccines; the formalin-inactivated RVFV vaccine TSI-GSD-200 requires three doses for protection, and the live-attenuated Smithburn vaccine has a risk to cause abortion and fetal malformation in pregnant ruminants. In this review, problems of traditional vaccines and the safety and efficacy of recently reported novel RVF candidate vaccines including subunit vaccines, virus vector, and replicons are discussed.